The Learning Style of Nursing Student in English for Nurses - Ni Wayan Novi Suryati; Kadek Maya Cyntia Dewi; I Putu Agus Endra Susanta (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2022)
This study aimed to describe the students' learning styles in learning English for Nurses (EFN) subject in the nursing study program. This study employed a descriptive design with a qualitative approach. There were 128 students recruited as the sample. Data were collected using open-ended questionnaires, interviews, observations and it was analyzed qualitatively. The finding of this study indicated that the majority of participants had a visual learning style 54 participants (42%), while the auditory learning style with 43 participants (34%) and 31 participants (24%) had kinesthetic learning style. This showed that each individual has a dominant learning style among visual, auditory and kinesthetic learning styles. It hoped that from the results of this study, the lecturer have more varied teaching materials and techniques that can be developed in order to keep up with the varied learning styles of students.